Coping Strategy Anak Berhadapan dengan Hukum Dalam Menjalani Pembinaan Di Lembaga Pembinaan Khusus Anak (LPKA) Kelas II Kota Bandung - Yuti Sri Ismudiyati; Enung Huripah; Tiara Devi Cristina Sihombing (Jurnal Ilmiah Rehabilitasi Sosial (Rehsos), 2025)
This research is entitled Coping Strategy of Children in Conflict with the Law During Rehabilitation at the Special Juvenile Rehabilitation Center (LPKA)Class II in Bandung City. Coping strategy refers to the ways individuals manage stress through problem-solving, emotional regulation, or spiritual approaches. This study aims to identify the coping strategies used by Children in Conflict with the Law (CICL) and to design an intervention program that strengthens their emotional and spiritual regulation during rehabilitation. The research used a descriptive quantitative approach, involving 139 male respondents undergoing rehabilitation at LPKA Class II Bandung. Data were colled using the validated instruments The Wyas Of Coping and The Brief RCOPE and analyzed through frequency distribution to assess the use of three coping strategy aspects: problem-focused, emotional-focused, and religious-focused coping. The results show that emotional-focused coping was categorized as high, while problem-focused and religious-focused coping were moderate. Children tended to respond to stress emotionally, but often in maladaptive ways such as self-blame, withdrawal, or avoidance. Additionally, spiritual values were not yet fully utilized as a source of strength or self-recovery.